2001
DOI: 10.1016/s0167-4889(01)00129-x
|View full text |Cite
|
Sign up to set email alerts
|

Disassembly of microtubules and inhibition of neurite outgrowth, neuroblastoma cell proliferation, and MAP kinase tyrosine dephosphorylation by dibenzyl trisulphide

Abstract: Dibenzyl trisulphide (DTS), a main lipophilic compound in Petiveria alliacea L. (Phytolaccaceae), was identified as one of the active immunomodulatory compounds in extracts of the plant. To learn more about its biological activities and molecular mechanisms, we conducted one-dimensional NMR interaction studies with bovine serum albumin (BSA) and tested DTS and related compounds in two well-established neuronal cell-and-tissue culture systems. We found that DTS preferentially binds to an aromatic region of BSA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0
13

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 16 publications
1
32
0
13
Order By: Relevance
“…8). DBTS is a bioactive natural compound found in a subtropical shrub, Petiveria Allieacea, which had been used as a folk medicine for antitumor and antirheumatic effects in Central and South America since the Aztecs (9). Primary bioactive compounds in the essential oil of the roots of this shrub include benzyldehyde, dibenzydisulfide, DBTS, cis-and trans-stilbene, and 2[(phenylmethyl)dithio]-ethanol.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8). DBTS is a bioactive natural compound found in a subtropical shrub, Petiveria Allieacea, which had been used as a folk medicine for antitumor and antirheumatic effects in Central and South America since the Aztecs (9). Primary bioactive compounds in the essential oil of the roots of this shrub include benzyldehyde, dibenzydisulfide, DBTS, cis-and trans-stilbene, and 2[(phenylmethyl)dithio]-ethanol.…”
Section: Introductionmentioning
confidence: 99%
“…Primary bioactive compounds in the essential oil of the roots of this shrub include benzyldehyde, dibenzydisulfide, DBTS, cis-and trans-stilbene, and 2[(phenylmethyl)dithio]-ethanol. DBTS is the principle bioactive compound in the lipophilic extract of plant roots (10,11) and its reported biological activities include enhancement of phagocytosis in treated mice (12), in vitro antifungal action mainly mediated by its derivative, methyl benzyl sulphonic anhydric (13), inhibition of neurite outgrowth and proliferation in neuroblastoma cell line, SH-SY5Y (9,11,14), and induction of monocyte-like differentiation of promyelocytic acute leukemia cell line, HL-60 (15). The molecular mechanisms underlying the biological activities of DBTS remain largely unknown, although it was reported that DBTS induced disassembly of microtubules and decreased the total expression of tubulin in SH-SY5Y cells, indicating that the antiproliferative activity of DBTS may result from its potential antimitotic effect (9).…”
Section: Introductionmentioning
confidence: 99%
“…15,16) Petiveria alliacea L. is included in the Brazilian and Paraguay Pharmacopoeias and by the Japanese Directory of Drugs.…”
Section: )mentioning
confidence: 99%
“…8) The recently reported studies of Benevides et al, 14) who isolated di-n-propyl disulfide, benzyl hydroxymethyl sulfide and several other antifungal polysulfides from the roots of Petiveria alliacea L., as well as the work of Szczepanski et al 12) Dibenzyl trisulphide, a main lipophilic compound in Petiveria alliacea L., has interesting biological activities, affecting, in addition to immunomodulation, microtubule-dependent cellular events and tyrosine phosphorylation-mediated MAP kinase signalling. 15,16) Petiveria alliacea L. is included in the Brazilian and Paraguay Pharmacopoeias and by the Japanese Directory of Drugs.…”
mentioning
confidence: 99%
“…On the other hand, components of the extracts have shown a well-defined antioxidant activity (Delle-Monache et al, 1996;Okada et al, 2008), as well as immunomodulatory (Quadros et al, 1999) and neuropharmacological activities (Cifuentes et al, 2001). Research in the last two decades focused on polysulfides with antineoplastic action produced in this species (MataGreenwood et al, 2001;Rosner et al, 2001;Ruffa et al, 2002;Williams et al, 2003;Williams et al, 2007;Webster et al, 2008).…”
Section: Introductionmentioning
confidence: 99%